Assessment of Frequency of Hepatitis C in Patients with Ischemic Heart Disease (Medical Forum Monthly, 2024)
Objective: Distribution of HCV in the patients of ischemic heart disease, and the effect that might further define the association between the two diseases.Study Design: A Cross sectional studyPlace and Duration of Study: This study was conducted at the General Medicine Department, Bolan Medical Complex Hospital Quetta from January 2024 to June 2024.Methods: out of 307 patients who had ischemic heart disease as the disease of interest.f interest. After 5 min of blood collection, venous blood specimens were tested for HCV antibodies using the ELISA test. The overall HCV positivity rate was determined and the result was statistics using Statistical Product and Service Solutions (SPSS) software where a ‘p’ value of < 0.05 was considered significant.Results: Among 307 patients, 28 (18.7%) were positive to HCV. The mean age of the patients was mean (SD, 60 ± 8.5 years). Lipid profile of HCV positive patients was mean cholesterol level 220 ± 15.7 mg/dL and in HCV negative it 205 ± 12.3 mg/dL significance value p = 0.04. The variation is presented by the standard deviation introduced for the cholesterol milestone, which points to the possibility of the HCV upsetting the lipid homoeostasis in these clients.Conclusion: The present study revealed nearly expected high level of HCV in patients of ischemic heart diseases so a possibility of HCV screening in such patients is warranted. Since lipid profiles are abnormal in patients with HCV, it may also be valuable to know what connect these two diseases.